2019
DOI: 10.5334/gjgl.246
|View full text |Cite
|
Sign up to set email alerts
|

V1 in Kipsigis: Head movement and discourse-based scrambling

Abstract: Kipsigis (Nilo-Saharan, Kenya) is a verb-initial language that exhibits a VSO/VOS alternation, in which the felicity of postverbal word orders is dependent on information structure. Specifically, the lexical item occupying the immediately postverbal position is discourse-prominent. We propose that V1 in Kipsigis results from head movement of the verb to a functional projection between TP and CP and that discourse-prominent material raises to Spec,TP. Movement to the immediately postverbal prominence position i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Their constraint on feature gluttony blocks derivations with multiple agreement/movement from converging at the interfaces, and is meant to capture Āextraction restrictions in certain Mayan languages. However, such a constraint is clearly not universal, as evidenced by the patterns discussed by van Urk and Richards (2015) and Bossi and Diercks (2019). Moreover, they propose that non-DPs as well as DPs are prevented from Ā-moving across DPs in Mayan, which is captured by their ban on multiple movements, and which is not the case in Tagalog.…”
Section: Conclusion -What Have We Learned?mentioning
confidence: 98%
“…Their constraint on feature gluttony blocks derivations with multiple agreement/movement from converging at the interfaces, and is meant to capture Āextraction restrictions in certain Mayan languages. However, such a constraint is clearly not universal, as evidenced by the patterns discussed by van Urk and Richards (2015) and Bossi and Diercks (2019). Moreover, they propose that non-DPs as well as DPs are prevented from Ā-moving across DPs in Mayan, which is captured by their ban on multiple movements, and which is not the case in Tagalog.…”
Section: Conclusion -What Have We Learned?mentioning
confidence: 98%
“…As for the syntactic properties of the language, Kipsigis is pro-drop, and the pragmatically unmarked word order is VSO (but it has extensive post-verbal scrambling; see Bossi & Diercks 2019). The language has the typologically rare marked nominative case system (see König 2006;Handschuh 2014), with nominative expressed tonally (Toweett 1979;Kouneli & Nie 2021;Jolin 2022).…”
Section: Conjugation Classes In Kipsigis: Not Therementioning
confidence: 99%
“…Composite probes, as van Urk [55] labels them, are two probes located on a single head, forming a probe conglomerate-an assumption that has been made for TMA-features on T or Infl already for a while (e.g., the combination of tense and φ-features on a single head; see also the more fine-grained approaches to φ-probes in, among many others, [60][61][62][63][64][65]). Although the CP has traditionally been treated as a pure A domain, more recently, it has been suggested that not only the inflectional domain can combine features on a single head, but that the C-domain can do so, too, in particular that A -features and A-features can form composite probes on C (among others [55,[66][67][68][69][70][71][72]). If a head carries such a composite A /A-probe, it triggers agreement (and movement) of mixed A /A-quality and therefore exhibits mixed A /A-properties.…”
Section: Composite Probes and Their Probing Propertiesmentioning
confidence: 99%
“…The C.R head in construction 5 carries the two probes [A ] and [A] which probe separately and independently from each other and can establish feature satisfaction with two different goals. This assumption follows Bossi and Diercks [70] who propose that in Kipsigis, a single head can carry two independent probes which can trigger agreement and movement independently of each other and with different goals. Following the nomenclature in [77,78], we call this probing process independent satisfaction.…”
Section: Composite Probes and Their Probing Propertiesmentioning
confidence: 99%